2017
DOI: 10.1002/eat.22712
|View full text |Cite
|
Sign up to set email alerts
|

Quality of randomized controlled trials in eating disorder prevention

Abstract: Given the majority of eating disorder prevention studies had problems with trial quality, it is recommended that future RCTs follow quality checklists and CONSORT guidelines, that RCTs are registered, and protocols published in advance. In addition, funding bodies are called on to deliver the support needed to ensure that preventions for eating disorders are efficiently and cost-effectively achieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 41 publications
1
12
0
Order By: Relevance
“…More recent RCTs of psychotherapy for EDs were more likely to have higher RCT‐PQRS scores. Similar findings were reported from meta‐analyses examining the quality RCTs of ED prevention (Watson et al, ) and of psychodynamic psychotherapy for a variety of mental illnesses (Kocsis et al, ). A likely explanation for this positive relationship is the implementation of quality checklists that have been developed over the years.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…More recent RCTs of psychotherapy for EDs were more likely to have higher RCT‐PQRS scores. Similar findings were reported from meta‐analyses examining the quality RCTs of ED prevention (Watson et al, ) and of psychodynamic psychotherapy for a variety of mental illnesses (Kocsis et al, ). A likely explanation for this positive relationship is the implementation of quality checklists that have been developed over the years.…”
Section: Discussionsupporting
confidence: 77%
“…The development of checklists and reporting guidelines may have had an impact on improving the quality of RCTs over time. For example, Watson et al () found that the quality of 96 RCTs of prevention programs for EDs was significantly and positively associated with publication year. However, the Cochrane tool and the CONSORT guidelines do not address quality issues specific to psychotherapy trials, such as length of follow‐up, the training or supervision of therapists, adherence to treatment manuals, or consideration of therapist and/or site effects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prevention and early intervention strategies are particularly pertinent given suggestions that neuroprogression may make symptoms more entrenched and less amenable to intervention over time [12]. A large body of research has evaluated preventative approaches for EDs, and selective prevention programs (i.e., those that target high-risk individuals/groups) have been shown to be most effective in reducing a range of psychopathology (e.g., body dissatisfaction, negative affect, and self-esteem [13,14]). These preventative approaches are informed by risk factor-related research.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18] However, today, there is a tendency for each research group only to evaluate data from their own field. [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] True randomized controlled trials allow healthcare providers to make informed inferences about the validity of these trials.…”
mentioning
confidence: 99%